Comparing Angiographic Devascularization with Histologic Penetration after Preoperative Tumor Embolization with Onyx: What Indicates an Effective Procedure? - Grandhi, Ramesh; Hunnicutt, Christopher T.; Harrison, Gillian; Zwagerman, Nathan T.; Snyderman, Carl H.; Gardner, Paul A.; Hartman, Douglas J.; Horowitz, Michael (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background and Purpose To assess Onyx (Covidien, Irvine, California, United States) efficacy as a preoperative embolic agent for neoplasms of the head, neck, and spine, and to compare angiographic and histologic evidence of tumor penetration as predictors of intraoperative blood loss.Materials and Methods Retrospective analysis of preoperative Onyx embolization procedures for treatment of head, neck, and spine tumors from 2009 to 2011. Patient demographics and information relating to the embolization procedure and operation were recorded. Measures of Onyx efficacy included intraoperative blood loss and length of surgery. Angiographic and histologic penetration, in addition to percentage of tumor devascularization, were assessed as predictors of efficacy.Results A total of 22 patients with 17 head or neck and 5 spinal lesions underwent trans-arterial preoperative Onyx embolization. Good angiographic penetration was reported in 41% of tumors and central histologic penetration in 59%, with mean tumor devascularization of 85.3% (standard deviation [SD]: 12.6%). There was no relationship between angiographic and histologic Onyx penetrance. Mean surgical blood loss was 1342 mL (SD: 1327 mL), and length of surgery was 289 minutes (SD: 162 minutes). Neither angiographic, nor histologic Onyx penetration predicted intraoperative blood loss (p = 0.38 and p = 0.32, respectively) or surgical length (p = 0.62 and 0.90, respectively). Devascularization was not associated with blood loss (p = 0.62), but it was a negative predictor of surgical length (p = 0.013).Conclusions Preoperative Onyx embolization of head, neck, and spine tumors is capable of deep histologic tumor penetration, even when not visualized on angiography. The lack of association between measures of procedural adequacy suggests that using angiographic devascularization as a measure of procedural efficacy may be of limited utility.
Keywords: Onyx; embolization; endovascular